Arabic Learning Experience For Students With Visual Impairments In State Islamic Universities/ ØªØ¬Ø±Ø¨Ø© ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù…Ø¹ÙˆÙ‘ÙŽÙ‚ÙŠÙ† Ø§Ù„Ø¨ØµØ±ÙŠØ© ÙÙŠ Ø§Ù„Ø¬Ø§Ù…Ø¹Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© - Zakiyah, Fitri; Sugiono, Sugeng; Mustofa, Tulus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This article aims to reveal the Arabic learning experience for visually impaired students in State Islamic Universities in Indonesia, including challenges faced by students, the advantages associated with them, and the opportunities from learning aspects. The researcher applied the descriptive method with the phenomenological qualitative approach. The observation, documentation, and in-depth interview are used to collect the data then analyzed qualitatively with Miles and Huberman's theory. The finding of this study shows the diversity of Arabic learning experiences for visually impaired students in Indonesia, which are influenced by the differences in educational and social background. Visually impaired students learned Arabic with constructivism and a collaborative approach. The challenges faced by students are the limited learning resources, including materials and media that can be accessed independently. The writer highlights the positive vibes of this case with the advantages associated with visually impaired students who are concerned with language generally as a primary means to connect with the world around them. They also have ultimate second language attainment, curiosity, and good language behavior to connect with their surrounding. In addition, they have an excellent intrinsic motivation in learning Arabic for religious reasons. Besides that, there are some great opportunities for them to get scholarships and good jobs as government workers.Â